Pemetaan Pelaku Usaha Mikro Dan Kecil Di Kecamatan Cicurug Kabupaten Sukabumi - Warcito, Warcito; Ikhwan, Khairul; Butarbutar, Parulian Halomoan (Jurnal Manajemen, 2020)
This study aims to map the potential of micro and small enterprises (MSEs) and describe the success of businesses in the area of assistance of the GNI Foundation in the villages of Nanggerang and Pasawahan Village, Sukabumi. This research is a quantitative descriptive study supported by qualitative data using mixed methods research. The research was carried out in two villages that were deliberately selected and became the area of assistance for the Indonesian Gugah Nurani Foundation (GNI), namely Nanggerang Village (Cibilik, Gintung, Nanggerang1, Nanggerang2) and Pasawahan Village (Pasawahan, Cibuntu, Selaawi, Sindang Palay) Cicurug District, Sukabumi Regency. Based on the survey results, the number of MSEs in the 2 (two) villages 171 businesses with potential in agriculture for Nanggerang village and food processing fields in Pesawahan village. Potential business opportunities in the villages of Nanggerang and Pasawahan villages at this time are the business of agricultural cultivation and food processing. This agricultural cultivation means businesses related to agricultural production such as organic vegetables or healthy vegetables, cultivation of healthy catfish (biofloc technology), healthy chicken cultivation, cultivation of sheep, goats and cows. Market-based agricultural business or market needs. The types of businesses mentioned above have broad market potential with clear target targets. The processed food business in question is a business managed by groups or individuals with local raw materials such as cassava and its derivatives, coconuts and derivatives, and processed fish products. The business success of MSEs in Nanggerang and Pasawahan villages is indicated by the business being run by its own business (86%), business duration of more than 10 years (33%) with a turnover of 1-10 million per month (47%) and contribution to income family more than 75% (37%).